Penatalaksanaan Fisioterapi pada Kasus Diabetes Melitus Tipe 2 dengan Metode Body Weight Training dan Senam Diabetes - Sefhia Lestary; Wanti Hasmar; Ucu Suherman (3031-8572, 2022)
DM Type 2 is diabetes caused by the body's failure to utilize insulin, which leads to increased blood sugar levels and decreased physical activity, Body Weight Training and Diabetes Gymnastics methods that can affect a person's body strength level, especially in leg muscle strength and high blood sugar levels. tall. To find out the management of physiotherapy in lowering blood sugar levels and increasing leg muscle strength using body weight training and diabetes gymnastics methods. After doing physiotherapy actions using body weight training and diabetes gymnastics with a dose of 3-5 times a week, the results showed an increase in leg muscle strength and a decrease in blood sugar levels. Body Weight Training and Diabetes Gymnastics can increase leg muscle strength and lower blood sugar levels.